Beyond Phishing: Detecting MFA Fatigue and Adversary-in-the-Middle at Scale - Angga Dipa Nagara, Angga Dipa Nagara; Tanti Suryawantie, Tanti Suryawantie; Andhika Lungguh Perceka, Andhika Lungguh Perceka; Jafar Muhamad, Jafar Muhamad (Karsa Husada Health Institute Garut, 2025)
Final-year students frequently experience anxiety and stress due to academic pressure related to thecompletion of scientific papers. If not managed appropriately, these conditions may negatively affectstudents’ mental health and academic progress. Butterfly Hug is a simple self-administered relaxationtechnique performed by crossing the arms over the chest and tapping alternately, producing a calmingeffect through bilateral stimulation. This technique is easy to perform, requires no equipment, and canbe applied in various situations. This study aimed to determine the effect of Butterfly Hug on anxietyand stress levels among final-year students at Karsa Husada Health Science Collage Garut in 2025. Theresearch design employed a one-group pretest–posttest design without a control group, involving 15respondents selected using Simple Random Sampling (SRS). The instruments used were the HamiltonAnxiety Rating Scale (HARS) to measure anxiety and the stress subscale of the DASS-21 to measurestress. The intervention was conducted consistently and in a structured manner for four days with initialguidance from the researcher. Data analysis using the Wilcoxon Signed Ranks Test showed a significantreduction in anxiety and stress levels. The significance values were 0.001 for anxiety and 0.002 forstress (p < 0.05), indicating that Butterfly Hug had a significant effect in reducing anxiety and stress.Therefore, this therapy is expected to serve as an alternative self-intervention that students can utilizeto maintain mental health while completing scientific papers.